Phenolic Compounds, Vitamins C and E and Antioxidant Activity of Edible Honeysuckle Berries (Lonicera caerulea L. var. kamtschatica Pojark) in Relation to Their Origin - Jana Orsavová; Irena Sytařová; Jiří Mlček; Ladislava Mišurcová (MDPI AG, 2022)
Honeysuckles are frost tolerant plants providing early-ripening fruits with health-promoting properties which have been used in traditional medicine in China. This study evaluates the impact of the climatic conditions of two areas on the chemical composition and antioxidant activity (AOA; by DPPH-2,2-diphenyl-1-picrylhydrazyl and photochemiluminescence assays) of eight cultivars of honeysuckle berries (Lonicera caerulea L. var. kamtschatica Pojark) of various ripening times. Expectedly, chemical composition and AOA values varied depending on the cultivars, locality and selected methods. Berries from Lednice (the area with more sunshine) showed higher average contents of total monomeric anthocyanins (TMAC; pH differential absorbance method), vitamins C and E and total phenolics (high-performance liquid chromatography). In contrast, berries from Žabčice (the area with more rain) performed higher average contents of total phenolics and flavonoids (UV/VIS spectroscopic analyses). Interestingly, fundamental amounts of chlorogenic acid were determined irrespective of the locality. Regarding TMAC and vitamin C content, early ripening Amphora from both areas has been assessed as the best cultivar; concerning the content of phenolic compounds, Fialka from both areas and Amphora from Lednice is considered as the most valuable. The obtained results may facilitate the selection of the most valuable cultivars for both producers and consumers.